Measuring Seclusion in Psychiatric Intensive Care: Development and Measurement Properties of the Clinical Seclusion Checklist - Ruud, Torleif; Haugom, Espen Woldsengen; Pincus, Harold Alan; Hynnekleiv, Torfinn (Frontiers in Psychiatry, 2021)
Background: Acute psychiatric units in general hospitals must ensure that acutely disturbed patients do not harm themselves or others, and simultaneously provide care and treatment and help patients regain control of their behavior. This has led to the development of strategies for seclusion of a patient in this state within in a particular area separated from other patients in the ward. While versions of this practice have been used in different countries and settings, a systematic framework for describing the different parameters and types of seclusion interventions has not been available. The aims of the project were to develop and test a valid and reliable checklist for characterizing seclusion in the context of inpatient psychiatric care. Methods: Development and testing of the checklist were accomplished in five stages. Staff in psychiatric units completed detailed descriptions of seclusion episodes. Elements of seclusion were identified by thematic analysis of this material, and consensus regarding these elements was achieved through a Delphi process comprising two rounds. Good content validity was ensured through the sample of seclusion episodes and the representative participants in the Delphi process. The first draft of the checklist was revised based on testing by clinicians assessing seclusion episodes. The revised checklist with six reasons for and 10 elements of seclusion was tested with different response scales, and acceptable interrater reliability was achieved. Results: The Clinical Seclusion Checklist is a brief and feasible tool measuring six reasons for seclusion, 10 elements of seclusion, and four contextual factors. It was developed through a transparent process and exhibits good content validity and acceptable interrater reliability. Conclusion: The checklist is a first step toward achieving measurements of seclusion. Its use in psychiatric units may contribute to quality assurance, more reliable statistics and comparisons across sites and periods, better research on patients’ experiences of seclusion and its effects, reduction of negative consequences of seclusion, and improvement of psychiatric intensive care.